Reproductive labors: the politics of women's health in South Africa, 1900 to 1960 - Burns Catherine Eileen (My University, 1995)
This dissertation opens the theme of reproduction in southern Africa to historical scrutiny. To do this, the work is divided into nine chapters, each tackling related aspects of this field of inquiry. It examines the development of a definition and practice of public health in the early decades of this century in Johannesburg and traces the local history of maternal health, mothercraft, and midwifery in the context of urban segregation. Healing practices that existed outside of official control, namely the work of family midwives and health practitioners many of whom were black women with skills and experience acquired in rural settings, are explored. Here, the commonplace separation of "Western biomedicine" and "indigenous African" practices concerning health and midwifery are challenged, using the records of an extraordinary herbalist and midwife, Louisa Mvemve. In 1928 the Bridgman Memorial Hospital was established as a site for a massive project to train and certify a cadre of black midwives and as space for scientific research concerning the bodies, birthing capacities, and gynecology of black women. The development of a local specialty termed "Bantu Gynaecology" is traced, indicating the powerful linkages between the development of anthropological and scientific knowledge about black women. The heart of this dissertation is an examination of the complex and contradictory history of the Bridgman through archival records and the oral testimony of women who trained at the Hospital and who gave birth there from 1930 to 1962. The politics of contraception and birth control in Johannesburg and the history of debates about sexuality and illegitimacy lead to a discussion of the increasingly didactic involvement of local and central state officials in the policing of black women in the city. This increasingly invasive state intervention in birth, "family planning" and controlling the reproductive labor of black women after 1950 is the subject of the last section.
Submitted to the graduate school in partial fulfillment of the requirements for the degree of DOCTOR OF PHILOSOPHY field of History Evanston, Illinois.